2012
DOI: 10.1021/ef201786v
|View full text |Cite
|
Sign up to set email alerts
|

Iron Transformation and Ash Fusibility during Coal Combustion in Air and O2/CO2 Medium

Abstract: Little work has been performed on the transformation of iron and ash fusibility during oxy-coal combustion, which is of great significance to assessing ash deposition propensity. A high-iron bituminous coal was burnt at 1300°C in a laboratory drop-tube furnace under four conditions: (1) 21 vol % O 2 /79 vol % N 2 (air-firing), (2) 21 vol % O 2 /79 vol % CO 2 (oxy-firing), (3) 27 vol % O 2 /73 vol % CO 2 (oxy-firing), and (4) 32 vol % O 2 /68 vol % CO 2 (oxy-firing). The bulk ash samples were subjected to X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…In NEW simulation, the fraction of AN magnetite to AN iron (magnetite fraction) was assumed to be 40% in offline estimation of the total and the soluble iron concentrations and their deposition flux. This magnetite fraction has not been constrained by observations and might be much higher or lower than 40% depending on the combustion sources 25 , 26 (Supplementary Note 1 ). We define the uncertainty range of the magnetite fraction between 20% and 80%, and discuss the total and the soluble iron estimates within this uncertainty range (Supplementary Note 1 ).…”
Section: Resultsmentioning
confidence: 96%
“…In NEW simulation, the fraction of AN magnetite to AN iron (magnetite fraction) was assumed to be 40% in offline estimation of the total and the soluble iron concentrations and their deposition flux. This magnetite fraction has not been constrained by observations and might be much higher or lower than 40% depending on the combustion sources 25 , 26 (Supplementary Note 1 ). We define the uncertainty range of the magnetite fraction between 20% and 80%, and discuss the total and the soluble iron estimates within this uncertainty range (Supplementary Note 1 ).…”
Section: Resultsmentioning
confidence: 96%
“…The drop tube furnace (DTF) used in this work is the same one as described elsewhere. 8 Briefly, the furnace tube has a length of 2 m and an inner diameter of 56 mm. It is electrically heated and the working temperature can be well-controlled.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In addition to natural sources, magnetite and hematite particles are also emitted through human activities involving combustion or other high‐temperature processes. Previously reported anthropogenic sources of these particles include integrated steel plants (Machemer, ), motor vehicle exhaust (i.e., the wearing down and melting of engine fragments; Liati et al, ), brake discs and brake pads in motor vehicles and trains (Karlsson et al, ; Kukutschová et al, ; Salma et al, ), welding operations in construction projects and industrial plants (Berlinger et al, ), and coal and heavy oil combustion (Fu et al, ; Linak et al, ; Yu et al, ). Hu et al () suggested that the dominant source of FeO x aerosols sampled in the Beijing metropolitan region was steel plants, which operated around their observatory at distances ranging from 6 to 25 km.…”
Section: Introductionmentioning
confidence: 99%